The Content Genre, Audience Share, and Presence of Public Sector Broadcasters in an Era of Overflowing OTT Services - Sungwook Park; Youngsun Kwon (International Telecommunications Society (ITS), 2023)
Various types of broadcasters have been created due to the progress of broadcasting technology, and recently, global OTT services have threatened the raison d'être of PSBs. PSB opponents, based on neo-classical economics, argue that the government's support for PSB hurts fair competition and distorts the market. In contrast, PSB proponents, based on neo-Keynesian economics, say that PSBs still need to provide citizens with quality programs for correcting market failures. This study found that several PSB channels broadcast entertainment much more than other genres in line with global OTT platforms except BBC One and Rai 1, and that the more PSB channels broadcast entertainment (quality programs), the higher (lower) annual audience share of channels. This could contribute to improving the management performance of PSBs. However, if the social agreement is reached that audience share is not the ultimate goal, it would be desirable for PSBs to consistently supply traditional quality content to citizens to prevent market failures.
Keywords: 330; content; genre; quality program; audience share; social responsibility; PSB; OTT